2020
DOI: 10.31002/metathesis.v4i1.1879
|View full text |Cite
|
Sign up to set email alerts
|

Mispronunciations in Graduate Students’ Presentation Projects

Abstract: <p class="AbstractText"><span lang="EN-GB">This paper explored the mispronunciations produced by Indonesian graduate students in their presentation projects. The data were collected from presentation projects of 11 graduate students of the English Education Master’s Program of Sanata Dharma University. The researchers used a document analysis as a technique to analyze the data. Results showed that 89 mispronunciations existed in the presentation projects. The mispronunciations were categorized into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…It was caused by the orthography in Bahasa Indonesia which rarely has a word with a consonant cluster at the end of the word, like /nt/ in the word /want/. This finding was also in line with the previous study by (Megariani et al, 2020) which found the same type of error in the word /ask/ that should be pronounced as /ɑːsk/ in British English and /aesk/ in American English, instead, students pronounced it as /ɑːs/.…”
Section: Percentage Of Students' Pronunciation Errorssupporting
confidence: 88%
See 2 more Smart Citations
“…It was caused by the orthography in Bahasa Indonesia which rarely has a word with a consonant cluster at the end of the word, like /nt/ in the word /want/. This finding was also in line with the previous study by (Megariani et al, 2020) which found the same type of error in the word /ask/ that should be pronounced as /ɑːsk/ in British English and /aesk/ in American English, instead, students pronounced it as /ɑːs/.…”
Section: Percentage Of Students' Pronunciation Errorssupporting
confidence: 88%
“…When the teachers can analyze the students' errors, it will get easier in creating the learning materials to help cope with the student's difficulties in learning. Furthermore, many studies have examined the errors in students' pronunciations (Sembiring & Ginting, 2016;Ramasari, 2017;Simarmata & Pardede, 2018;and Megariani et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also assumed that there were no mispronunciation errors due to the level of college students who have a basic understanding of pronunciation if there are still pronunciation errors. It is also supported by Megariani et al (2020) that many students did mispronunciations commonly when they did presentation projects. This has a relationship with the research conducted by the researcher, namely, students still use dialects in their home regions in English pronunciation.…”
Section: Difficulty In Pronouncing Consonants and Vocal Sounds Correctlymentioning
confidence: 87%
“…Megariani et al proposed that the components of phrase word bits include nouns, verbs, adjectives, and complement components. e word bits of the phrase are called patterns [15]. Balakrishnan et al [16] used the Bank of English corpus to summarize and analyze the valence patterns of 274 nouns, 511 verbs, and 544 adjectives in English and pointed out that the element code similarity in English coding method and pattern grammar is high.…”
Section: Related Workmentioning
confidence: 99%